Electronic "Bridge" Construction via Ag Intercalation to Diminish Catalytic Anisotropy for 2D Tin Diselenide Cathode Catalyst in Lithium–Oxygen Batteries. Issue 27 (7th June 2022) - Zhang, Guoliang; Liu, Chengyan; Guo, Liang; Liu, Ruowei; Miao, Lei; Dang, Feng
Abstract: As cathode catalysts for lithium–oxygen batteries (LOBs), 2D materials are attracting significant attention due to their layered structures, tunable surface chemistry, and unique electronic states. However, catalytic anisotropy, particularly the poor catalytic capability of the van der Waals forces contained in stack edge planes, has suppressed the enhancement of LOB performance as 2D cathode catalysts. Here, an ion‐intercalation strategy is proposed to diminish the catalytic anisotropy of 2D materials. Ag ions are successfully intercalated into SnSe2 layered structure and regulate the electronic states between stack edge planes, leading to an improvement in the catalytic capability of 2D SnSe2 . Notably, the catalytic capability of the 2D surface (001) plane of SnSe2 is also significantly enhanced after Ag intercalation, which can efficiently accelerate charge transfer and suppress the passivation on the 2D surface plane during the oxygen reduction/evolution reaction process. As a consequence, the Ag‐intercalated SnSe2 cathode exhibits superior specific capacity of 16871 mAh g −1 and an ultrastable cycle life over 2300 h at a current density of 100 mA g −1 and 144 cycles at current density of 1000 mA g −1 . This work provides insights into the modulation of the catalytic capabilities of 2D materials, which have significant potential for this application in LOBs. Abstract : 2D SnSe2 with Ag intercalation between stack octahedral layers is synthesized and used as a cathode for lithium oxygen batteries. In experiments, the 6Ag‐SnSe2 electrode achieves ultralong cycle life over 2300 h. Theoretical calculations certify that the Ag‐ions act as an electronic "bridge" and regulate the surface electronic state of SnSe2, enhancing the catalytic capability of the surface (001) plane and preventing passivation of the (100) plane.